Faktor-faktor yang berhubungan dengan pemberian susu formula pada bayi usia 0-6 bulan - Rika Yulendasari; Muhammad Firdaus (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Maternal factors relating to milk formula feeding on infants aged 0-6 months in Lampung-IndonesiaBackground: Many parents assume that breastmilk only would not be sufficient to fulfil baby’s nutrition need, so that baby need to feed with complementary feeding. The administration of complementary feeding like formula milk has been a common practice for some parents with reasons including less breastmilk production, maternal busy activities, less maternal knowledge concerning breastmilk feeding, saving time, being attracted by offered formula milk. Most parents administer formula milk with amount almost similar to breastmilk to fulfil the baby’s need. Purpose: Knowing factors of formula feeding for infants 0-6 months.Methods: This was a quantitative analytic research by using cross sectional approach. Population was 220 babies of 0-6 months old in Waykandis public health centre working area from January to April 2019. 142 respondent samples were taken by using proportional random sampling.Results: The statistic test result showed that there were correlations of maternal occupation (p-value 0.016; OR 2.485), maternal education (p-value 0.004; OR 2.886), maternal knowledge (p-value 0.000; OR 0.089) to formula milk administration.Conclusion: There were factors of formula feeding for infants 0-6 months. The researcher expects the public health centre to create a schedule list for complementary feeding besides breast milk administration according to the children fewer than five needs, and to be always active in providing health education especially concerning the importance of formula milk knowledge.Keywords: Maternal; Formula Feeding; Infants 0-6 MonthsPendahuluan : Banyak orang tua menganggap bahwa kebutuhan nutrisi bayi tidak cukup hanya dengan ASI, sehingga bayi perlu dibantu dengan memberikan makanan pendamping ASI. Pemberian makanan pendamping ASI berupa susu formula sudah menjadi hal yang biasa, dengan berbagai alasan yang diberikan seperti ASI yang keluar sedikit, kesibukan ibu, kurangnya pengetahuan ibu tentang pemberian ASI, hemat waktu, tergiur dengan kandungan susu formula yang ditawarkan. Kebanyakan orang tua menilai pemberian susu formula hampir setara dengan ASI dan dapat mencukupi kebutuhan gizi bayinya. Tujuan : Diketahui faktor-faktor yang berhubungan dengan pemberian susu formula pada bayi usia 0-6 bulan.Metode : Jenis penelitian kuantitatif. Rancangan menggunakan analitik, dengan pendekatan cross sectional. Populasi dalam penelitian seluruh bayi usia 0-6 bulan di wilayah kerja Puskesmas Waykandis dari bulan Januari sampai dengan bulan April 2019 yaitu sebanyak 220 orang. Sampel berjumlah 142 responden dengan teknik Proportional Random Sampling.Hasil : Berdasarkan hasil uji statistik, terdapat hubungan antara faktor pekerjaan dengan pemberian susu formula (p-value 0,016) nilai OR 2,485, terdapat hubungan antara faktor pendidikan dengan pemberian susu formula (p-value 0,004) nilai OR 2,886, terdapat hubungan antara faktor pengetahuan dengan pemberian susu formula (p-value 0,000) nilai OR 0,089.Simpulan : Ada hubungan antara faktor pekerjaan, pendidikan dan pengetahuan terhadap pemberian susu formula pada bayi 0-6 bulan. Diharapkan tenaga kesehatan dapat membuat daftar menu pemberian MP-ASI sesuai dengan kebutuhan balita, selalu aktif memberikan penyuluhan kesehatan pentingnya pengetahuan tentang susu formula.